ANALISIS SPASIAL CADANGAN KARBON BAWAH PERMUKAAN LAHAN GAMBUT BERBASIS SISTEM INFORMASI GEOGRAFIS DI ZONA TRANSISI GAMBUT–MINERAL DESA PANDAN MAKMUR - Hidayat, Angga; Mastur, Agus Kurniawan; Ibrahim, Muhammad adithia; Latif, Muhammad; Putri, Nur Rahmi Azqiya; Syakirah, Syakirah (Universitas Batanghari Jambi, 2026)
Tropical peatlands are among the largest terrestrial carbon reservoirs; however, their existence is increasingly threatened by hydrological alteration and intensive land-use practices. Pandan Makmur Village, Geragai District, East Tanjung Jabung Regency, is located within a transitional peat–mineral landscape dominated by oil palm plantations and functions as a buffer zone for the Sungai Buluh Peatland Protected Forest. This condition renders the area both strategically important and highly vulnerable to peatland degradation and subsurface carbon loss. This study aims to analyze the magnitude and spatial distribution of subsurface carbon stocks in peatlands using a Geographic Information System (GIS)-based approach. The study employed a semi-detailed soil survey method with a systematic grid design of 700 × 700 m. Field data included peat thickness, peat maturity level, bulk density, water content, and organic carbon (C-organic) content, analyzed at two soil depths: 0–30 cm and 30–60 cm. All parameters were integrated into a raster-based GIS with a spatial resolution of 20 × 20 m to calculate and map subsurface carbon stocks spatially. The results show that peat and peaty soils in Pandan Makmur Village cover approximately 1,048.7 ha and are predominantly composed of thin to shallow peat with a sapric maturity level. The total subsurface carbon stock is estimated at 370,566 tons, with the largest contribution originating from the 0–30 cm layer (93.2%), while layers deeper than 30 cm contribute only 6.8%. At the same thickness, the surface peat layer stores nearly twice as much carbon as the underlying layer. These findings confirm that the upper peat layer is the primary carbon storage compartment and simultaneously the most vulnerable to carbon loss. Therefore, protection of the surface peat layer and sustainable water management are essential for carbon emission mitigation and sustainable management of transitional peatland ecosystemsKeywords : Activation, Adsorption, Crude Glycerol, Natural Zeolite from Malang